A decrease in the prevalence and severity of vibration-induced white fingers among lumberjacks in Finland. - Pyykkö, Ilmari; Sairanen, Eero; Korhonen, Olli; Farkkila, Markus; Hyvärinen, Juhani (Scandinavian Journal of Work, Environment & Health, 1978)
One hundred and eighty-seven lumberjacks in eastern Finland and 582 lumberjacks (in two groups of 501 and 81) in different parts of Finland were studied. In the first part of the study with 187 lumberjacks the prevalence of vibration-induced white fingers (VWF) was decreased from 40% in 1972 to 25% in 1975. Retrospectively, the attacks of VWF became more common after 1965, the number of attacks being highest in 1970-1972. The severity of VWF among men who still had attacks was reduced in 1975 in comparison to 1972. The latent period of VWF was about 5,500 chain saw operating hours, which corresponds to five years of operating time, both in 1972 and in 1975. In the second part of the study 40% of 501 lumberjacks had had symptoms indicating VWF during the last two years. The severity of VWF was reduced in half of the subjects with VWF, but the reduction was not as marked as in the first part of the study. Numbness of hands and arms was present in more than half of the subjects in both phases of the study. No evident relief of this symptom had occurred during the follow-up period. The most probable reason for the decrease in the prevalence of VWF appeared to be the vibration damping of chain saws introduced in 1969. In part two of the study 81 lumberjacks had used only antivibration saws. The prevalence of VWF among them was 16% after an exposure time which equaled the mean latent period of VWF.
Keywords: chain saw; Finland; lumberjack; vibration disease; vibration-induced white finger